Digital storytelling: an influential reading comprehension and creativity tool for the 21st century literacy skills - Rofiza Aboo Bakar (UPT Bahasa Universitas Tanjungpura, 2019)
Digital storytelling has been proposed as an influential language learning tool that can facilitate learners’ reading comprehension and creativity. There is an interplay between digital storytelling and comprehension. Likewise, there is a connection between digital storytelling and creativity. However, this chemistry that exists is far more complex than previous studies have expressed. This paper puts forth a novel model by which to honor the inter-relationship among digital storytelling, reading comprehension and creativity. The model proffers a practical aim that can allow teachers to recognize and applaud students’ effort whenever they create their digital storytelling, for comprehension and creativity, among other 21st-century literacy skills, have simultaneously and ideally taken place.